Prototype Corn Drying Hybrid of Solar Energy and Turbine Ventilator - Isman Harianda; Moch. Agus Zaenuri (SENATIK STT Adisutjipto, 2019)
The sunlight that enters through the transparent glass will heat the Greenhouse Effect room, the air in the room will become hot, then the hot air naturally (air density becomes low) will rise upward following the slope of the transparent glass than through the Drying Rack while drying the corn. After passing through the Drying Rack continue to go above and out through the Turbine Ventilator, this Turbine will automatically move due to the pressure of the hot air coming out, and the turbine will rotate continuously if air temperature  is inside in the drying room larger than the outside air, and if there is wind speed around the Ventilator Turbine. The results of this study obtained a drying rate of 3.77 grams / minute and the efficiency of the corn drying equipment system was 52%, to use a Turbine Ventilator, whereas without using a Turbine Ventilator, the drying rate was 4.23 grams / minute and the efficiency was 32%.